Analisis Faktor-Faktor Yang Berpengaruh Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan - Novita Hana Putri; Johandri Iqbal; Ferdyan Wana Saputra (Journal of Applied Accounting And Business, 2024)
This research aims to analyze the factors that influence the timeliness of submitting financial reports to oil palm plantation companies listed on the Indonesia Stock Exchange in 2020-2022. The population in this study were 28 oil palm plantation companies listed on the Indonesia Stock Exchange. The sample was determined based on the purposive sampling method, with a total sample of 19 oil palm plantation companies so that the total observations in this study were 57 observations. Researchers used logistic regression analysis techniques. The research results simultaneously show that profitability and leverage have no effect on the timeliness of submitting financial reports. The partial research results show that profitability has no effect on the Timeliness of Submission of Financial Reports and leverage has no effect on the Timeliness of Submission of Financial Reports